Design an Android Application to Read Banknotes for the Blind and Visually (Cash Reader) - Ben Neji, Ola Ali; Baraka, Ali Ahmed; Aziz, Arwa Al-Sidik; Al-Dabaa, Fatima Hussian (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This research aims to design an application for recognition of Libyan cash currency. It works on Android System for blind and sight weak people. The idea of the application is enabling those people of recognizing all local Libyan currency categories by using technology assistance that is already used in the application which is by its role includes extracting the text from the image as well as extracting Algorithms of the search out of the currency text within the extracted text and its conformity which helps for reading the currencies loudly and much easier. Due to the clarity of the requirements of this system, the waterfall model methodology has been used as an executive model of the system. As an inform Data were collected to design and identify the requirement of the system by using personal interview method which is conducted with visual disability that are existed AL-Hama organization. As a result of it, wide range of answers are collected. These answers are formed the basic stone towards starting the processing the problem through this search. As a successful step, the general research has also been taken advantage of different sources of information. This search follows the method of analytical description for tracking previous studies as well as studying and analyzing them. Experimental approach to analyze the system and (UML) language are used. Then, designing the system through an Android studio program by using Java software. Next, this system is linked with a Firebase. Lastly, the partial and full testing of this system has been done in purpose of discovering and processing errors. As a result, this search gained consequences and the most important of them represented in accessing to design easy-use application in order to take in account blind people as it is free of complexity and treats the problems that blind people are suffer from especially currency paper in a way that saves their money and avoids them theft. This search recommended some tips that time did not allow for achieving them which are making the application works by audio orders in order to make it easier for targeted people. In addition, it recommends feature OD recognition forged currency and alerting the blind person about it.
Keywords: The blind; Visually impaired; Coins; Text extraction algorithm; Smartphone application